AN ANALYSIS OF DIFFERENCE OF RELIGION AS A DISQUALIFICATION FROM INHERITING IN TERMS OF THE ISLAMIC LAW OF SUCCESSION: A SOUTH AFRICAN CASE STUDY - Muneer Abduroaf (Obiter, 2023)
A Muslim man can marry a maximum of four women at a time in terms of Islamic law. These women may include Muslim women, Christian women, and Jewish women. It is noted that a Christian and Jewish widow would not inherit from the intestate estate of her deceased Muslim husband in terms of the Islamic law of intestate succession. This article analyses the problems with this type of discrimination within the South African context. Interfaith marriages between Muslims and non-Muslims are looked at first. Then the disqualification of a Christian widow inheriting from her deceased Muslim husband’s estate in terms of the Islamic law of intestate (compulsory) succession and testate (optional) within the South African context is discussed. The article concludes with an overall analysis of the findings and makes a pertinent recommendation.